Androgenetic alopecia: combing the hair follicle signaling pathways for new therapeutic targets and more effective treatment options. (2nd September 2019) - Vasserot, Alain P.; Geyfman, Mikhail; Poloso, Neil J.
ABSTRACT: Introduction : In the past 30 years, only two drugs have received FDA approval for the treatment of androgenetic alopecia reflecting a lack of success in unraveling novel targets for pharmacological intervention. However, as our knowledge of hair biology improves, new signaling pathways and organogenesis processes are being uncovered which have the potential to yield more effective therapeutic modalities. Areas covered : This review focuses on potential targets for drug development to treat hair loss. The physiological processes underlying the promise of regenerative medicine to recreate new functional hair follicles in bald scalp are also examined. Expert opinion : The discovery of promising new targets may soon enable treatment options that modulate the hair cycle to preserve or extend the growth phase of the hair follicle. These new targets could also be leveraged to stimulate progenitor cells and morphogenic pathways to reactivate miniaturized follicles in bald scalp or to harness the potential of wound healing and embryogenic development as an emerging paradigm to generate new hair follicles in barren skin.